Tuning residual chirality in carbon dots with anti-microbial properties. Issue 53 (1st September 2020) - Victoria, Florence; Manioudakis, John; Zaroubi, Liana; Findlay, Brandon; Naccache, Rafik
Abstract : Chiral carbon dots, prepared from the unnatural d -enantiomer of cysteine, inhibit the growth of Escherichia coli ATCC 25922 and MG1655 at a lower concentration than l -carbon dots, prepared from the l -enantiomer. Abstract : Chirality remains a critical consideration in drug development and design, as well as in applications of enantioselective recognition and sensing. However, the preparation of chiral nanomaterials requires extensive post synthetic modifications with a chiral agent, coupled with extensive purification. This limits the use and application of chiral nanomaterials. Herein, we report a facile, one-step microwave-assisted synthesis of chiral carbon dots through the reaction of l - and d -cysteine amino acid precursors and citric acid. We modulated the synthetic parameters to preserve and tune the residual chiral properties of the dots and demonstrate that the reaction conditions play a critical role in dictating the chiral behaviour of the dots. Finally, in a proof of concept application we demonstrated that the synthesized carbon dots, particularly d -carbon dots inhibit bacterial growth at a lower concentration than l -carbon dots. By varying bacterial strains and chirality of the carbon dots, concentrations ranging from 0.25–4 mg mL −1 of the nanoparticles were required to inhibit microbial growth. The ability to preserve and tune chirality during synthesis can open up novel avenues and research directions for the development of enantioselective materials, as well as antibacterial films and surfaces.